Analisis Integrasi SDGs dan ESG dalam Laporan Keberlanjutan PT Telkom Indonesia (Persero) Tbk Tahun 2022–2024: Perspektif Akuntansi Keberlanjutan - Rury Rizki Handayani; Elsya Fitrianisa (Indo Publishing, 2025)
This study aims to analyze the integration of Sustainable Development Goals (SDGs) and Environmental, Social, and Governance (ESG) performance in the sustainability reports of PT Telkom Indonesia (Persero) Tbk for the 2022–2024 period using a qualitative content analysis approach. The research focuses on how sustainability accounting is applied to measure and report non-financial performance in a transparent and accountable manner. The findings indicate that Telkom has adopted various sustainability indicators in its business strategy, particularly in areas such as digital transformation, energy efficiency, and community empowerment. However, challenges remain, including limited quantification of social and environmental impacts and the need to enhance reporting capacity. This study recommends strengthening the integration of sustainability accounting systems, leveraging digital technology for data collection, and developing qualified human resources. These insights are expected to contribute to the improvement of sustainability reporting practices in both state-owned and private enterprises.